A Commercially Available Portion-Controlled Diet Program Is More Effective for Weight Loss than a Self-Directed Diet: Results from a Randomized Clinical Trial - Cook, Chad M.; McCormick, Courtney N.; Knowles, Mandi; Kaden, Valerie N. (Frontiers in Nutrition, 2017)
Objective: To examine changes in weight and related outcomes in response to a commercial weight loss program compared to a self-directed diet in adults with overweight or obesity. Design: Participants were randomly assigned (stratified by body mass index [BMI] and age) to a commercial weight loss program (n = 38) or to a self-directed Dietary Approaches to Stop Hypertension (DASH) diet (n = 40) for a 16-week period. Daily energy intake goals were 1,50 kcal/d for men and 1,200 kcal/d for women, except for the first week of the commercial program (1,000 kcal/d). This study was registered at ClinicalTrials.gov (NCT03017443). Participants: Primarily Caucasian (71%) women (n = 61) and men (n = 17) from the greater metropolitan area of the city of Chicago, IL, U.S.A. with a mean baseline BMI of 34.4 kg/m2, body weight of 95.7 kg, and age of 50.4 y. Results: Data = mean (95% CI). At week 16, the commercial program group lost significantly more body weight [-5.9 (-7.5, -4.3) kg vs. -1.8 (-2.9, -0.8) kg; or -6.4% vs. -1.8% of initial body weight, respectively], fat mass [-4.4 (-5.7, -3.1) kg vs. -1.2 (-2.1, -0.4) kg] and total body circumference (chest + waist + hip + upper arm + thigh) [-16.9 (-21.5, -12.3) cm vs. -5.8 (-9.0, -2.6) cm] (p < 0.01 for all). Additionally, more participants in the commercial program group lost a clinically meaningful amount of weight, defined as ≥5% of initial body weight, at week 16 (58% vs. 13%, p < 0.001). Conclusion: The commercial program resulted in greater weight loss and improvements in body composition/anthropometric parameters compared to a self-directed DASH diet over a 16-week period. Some important limitations were that no objective measurements of dietary intake or physical activity were collected to potentially ascertain the independent or combined effects of these components on weight loss (or lack thereof). Additionally, future research is warranted in order to understand the effects of this program, and similar programs, on longer-term changes in body weight, in particular weight loss maintenance, as weight regain is common following the cessation of a structured weight loss intervention.